Measurement of aquatic competence in infant and children between 6 months and 14 years. A systematic review. - Daniel Juárez Santos-Garcia; Osvaldo Rocca; Archit Navandar; Juan Antonio Moreno Murcia (Desafio Singular, 2022)
The objective of this study was to carry out a systematic review of the literature on tools for measuring aquatic competence in infants and children between the ages of 6 months to 14 years old. A systematic review was carried out following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Of the eight studies selected, six obtained high valuations based on the Downs and Black Quality Assessment checklist. The studies were classified into three categories, one that proposed tools that measured actual aquatic competence (n=6), other one that measured perceived aquatic competence (n=1), and the other that measured both (n=1). Five of the studies measured emotional, social, cognitive, and communicative skills apart from motor skills. A majority of the studies focused the proposed assessment tool on a specific age group, while two studies looked at a broader age group.